2020
DOI: 10.1186/s13213-020-01588-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different abiotic stresses on carotenoid and fatty acid metabolism in the green microalga Dunaliella salina Y6

Abstract: Purpose: Under different abiotic-stress conditions, the unicellular green microalga Dunaliella salina accumulates large amounts of carotenoids which are accompanied by fatty acid biosynthesis. Carotenoids and fatty acids both possess long carbon backbones; however, the relationship between carotenoid and fatty acid metabolism is controversial and remains poorly understood in microalgae. Methods: In this study, we investigated the growth curves and the β-carotene, lutein, lipid, and fatty acid contents of D. sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 49 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…It is a known fact that the production of these carotenoids in Dunaliella salina increases with increasing light intensity. Thus, an increase in lighting from 100 to 200 µmol photons m −2 s −1 increased the accumulation of β-carotene in Dunaliella salina Y6 by 31.5% [79]. In other studies, Dunaliella strains (DF15, DF17, DF40, UTEX 253) demonstrated an increase in β-carotene productivity under lighting of more than 200 µmol photons m −2 s −1 and maximum productivity values (up to 3.5 mg L −1 day −1 ) were noted at 1500 µmol photons m −2 s −1 [48].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 93%
See 3 more Smart Citations
“…It is a known fact that the production of these carotenoids in Dunaliella salina increases with increasing light intensity. Thus, an increase in lighting from 100 to 200 µmol photons m −2 s −1 increased the accumulation of β-carotene in Dunaliella salina Y6 by 31.5% [79]. In other studies, Dunaliella strains (DF15, DF17, DF40, UTEX 253) demonstrated an increase in β-carotene productivity under lighting of more than 200 µmol photons m −2 s −1 and maximum productivity values (up to 3.5 mg L −1 day −1 ) were noted at 1500 µmol photons m −2 s −1 [48].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 93%
“…Algae grown under various light intensities show changes in biomass formation rate, pigment and lipid content, fatty acid composition, and ratio. For this purpose, various researchers have studied a fairly wide range of light intensity: from 5 to 3500 µmol photons m −2 s −1 [31,43,47,53,[77][78][79][80].…”
Section: Optimal and Photoinhibiting Light Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…Samples of the microalgae were taken every other day to monitor the cells' dry weight (DW). DW was measured according to the method described by Wu et al [33]. Briefly, 5 mL microalgae suspension was filtered through a preheated (105 °C, 24 h), preweighed glass microfiber filter (Whatman GF/C, 47 mm, UK).…”
Section: Water Reusementioning
confidence: 99%